A CFD model to assess lower Granite Dam operations under stratified conditions. Issue 4 (1st October 2020) - Politano, Marcela; Laughery, Ryan
Abstract : Elevated water temperature has deleterious effects on cold-water fish. Lower Granite (LWG) is a run-of-the river dam in the Pacific Northwest, USA. LWG impounds a reservoir, with capacity of 5.7×10 8 m 3, that often become stratified. This paper presents a numerical model to assess LWG selective withdrawal operations to minimize thermal effects on fish. The model accounts for buoyancy forces, which are dominant at low river flowrates. The thermal model was validated against forebay temperature profiles and tailrace temperature on 3 July 2015. Twenty-six simulations were performed under different dam operations, stratification intensities and river flowrates. Numerical results indicate that the thermal stratification has a strong effect on the withdrawal region. Under stratified conditions, a high velocity layer at the intake elevation impacts the hydrodynamics and thermal capacity of the reservoir. According to the simulations, flow uniformly distributed across odd numbered powerhouse units is the best configuration to reduce downstream temperature.